Learning Curve Assessment for Percutaneous Left Atrial Appendage Closure With the WATCHMAN Occluder. (29th June 2016) - Ledwoch, Jakob; Krollmann, Christine; Staubach, Stephan; Hug, Martin; Strohm, Henning; Mudra, Harald
Abstract : Objectives: We sought to evaluate the effect of increasing experience with left atrial appendage (LAA) closure on short‐term outcome. Background: Data regarding the impact of the learning curve of LAA closure—particularly regarding technical aspects of the procedure—are lacking. Methods: The present analysis represents first data from a single‐center all‐comer registry. The population was divided into 3 groups according to treatment time (group 1: patients 1–30; group 2: patients 31–60; group 3: patients 61–90). Results: The mean age of the population was 77 years. Median CHA2 DS2 VASC Score and HAS‐BLED were 5 (IQR 3–5) and 3 (IQR 3–4), respectively. Implantation success was 90% with a slight but not statistically significant increase during the course of the registry. Procedure time (75 [62–108] vs. 50 [43–66] vs. 47 [41–61] minutes; P < 0.0001), fluoroscopy time (20 [15–30] vs. 11 [8−19] vs. 11 [9–18] minutes; P = 0.002), and contrast volume (105 [70–170] vs. 60 [50–75] vs. 50 [50–73] ml; P < 0.0001) were reduced across the 3 groups. In‐hospital complications decreased significantly (20 vs. 7% vs. 0%; P = 0.021). The compression grade of the occluder was chosen higher with increasing learning curve (15 [11–25] vs. 25 [17–29] vs. 21 [14–26] %; P = 0.05). Conclusions: With increasing operator experience the performance and safety of percutaneous LAA closure improved continuously.